Aspek Semantik dalam Teks-teks Agama Buddha: Analisis Makna, Simbolisme, dan Tafsiran melalui Pendekatan Hermeneutik - Kartono Kartono (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This study examines the semantic dimensions in Buddhist religious texts, focusing on linguistic meaning, symbolism, and interpretation. Applying theoretical frameworks of semantics (lexical semantics, semiotics) and qualitative hermeneutical methodology, this research aims to understand how Buddhist teachings are constructed in texts and interpreted by Buddhist communities. The findings indicate that key texts such as the Sutta Pitaka and Mahāyāna Sūtras contain multiple layers of meaning that depend on cultural context, ritual practices, and teacher interpretations. This research supports the development of interdisciplinary understanding between linguistics, religious studies, and Buddhist practice. The study reveals that meaning in Buddhist texts operates on three distinct levels: literal (vācika), contextual (attha), and spiritual (paramārtha), each requiring different hermeneutical approaches. Symbols such as the lotus and the Dharma wheel function not merely as metaphorical ornaments but as carriers of profound cosmological and soteriological significance